Perubahan Sosial Akibat Perkembangan Pariwisata Pantai Di Dusun Karanggongso, Desa Tasikmadu, Kabupaten Trenggalek - Marifatul Nikmah; Kliwon Hidayat; Edi Susilo (Jurnal Ekonomi Pertanian dan Agribisnis, 2023)
Resources that have been provided by nature have a potential to be developed to support human life. One of them is the coastal area that can be developed, namely Karanggongso Beach in trenggalek. This research examines social change that occurs as a result of development of tourism on Karanggongso Beach. The rapid development of tourism brings many changes to the condition of society (Ini yang berubah kebiasaan? Kalo iya tambahin habit dibelakangnya). This research focused on social change that occurred in 2010 - 2020 in line with the development of tourism in Karanggongso beach. This research uses a qualitative approach. Data collection methods used in this research are interview, observation, and documentation. The results show tourism changes occurred since Karanggongso became accessible to local or non-local tourists.Changes that occur due to the existing facilities such as infrastructure improvement, attraction, various tourist rides, various photo spots, good kiosk arrangement and adequate sanitation. Due to facilities and infrastructures, attracted visitors, thereby causing cultural, interactional, and structural changes. Social changes that happen namely diversification of livelihood, division of labor, hospitality, education, language, lifestyles, and interaction with nature. Those changes can affect the sustainability of tourism and the condition of the community in the future so it needs to be guided and managed properly by all related parties.